ISPC Criteria for Review of CRP II Pre-Proposals - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
The ISPC will follow the criteria listed in the Guidance document and analyze the proposed evolution of each CRP compared to the first set of proposals both in terms of its individual merit and its contribution to the SRF and the overall system portfolio.